Analysis of Factor Affecting The Willingness of HIV Test on Mariners - Utami, Putri Intianti; Wahyuni, Chatarina Umbul; Widati, Sri (Health Notions, 2018)
Proportion of mariner that was willing to take HIV test was under 35% of mariners offered by health workers for test when performing medical check-up. The purpose of this study was to analyze the factors that affect the willingness of HIV testing on mariners at PHC Hospital Surabaya. The type of this research was analytic observational research with cross sectional research design. The population of this study were all mariners who performed medical check-up and offered for HIV testing at Primasatya Husada Hospital Citra Surabaya on July until October 2017. The sample of this study was several mariners who performed medical check-up and offered for HIV testing on July until October 2017. Sampling technique used was consecutive sampling and obtained 130 respondents. Based on the result of multivariable analysis, the results showed that the factors that affect the willingness of HIV test on mariners are low self-stigma p = 0.001 and PR = 3.513, CI 95% : 1.645-7.502, perception of high susceptibility to HIV p = 0.00 and PR = 4.640, CI 95%: 2.180-9.875, perception of high test benefit p = 0.00 and PR = 4.168, CI 95%: 1.958-8.872, good friend support p = 0.003 and PR = 3.022, CI 95%: 1.460-6.258. The necessity of declining HIV test counseling on mariners about the benefits of testing, HIV risk factors, and HIV testing principles especially regarding the confidentiality of HIV test results. Formation of trained peer education originating from mariners to provide information about HIV and encourage HIV testing of mariners.